2019
DOI: 10.1002/cpe.5317
|View full text |Cite
|
Sign up to set email alerts
|

Parallel simulation of the synchronization of heterogeneous cells in the sinoatrial node

Abstract: The cells of the sinoatrial node (SAN) are self-excitable entities that show a coupled electrical pattern that consists of the synchronized activation of action potentials that determine the heart rate. To accurately describe the behavior of cell membrane proteins, theoretical biophysicists have devoted themselves to the study of the electrical activity of individual cells, which involves solving a large number of coupled differential equations. This computational limitation makes the modeling of a large numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Multicellular numerical models of SAN function have been developed in 1 dimension (as a linear chain of consecutive SAN cells) [49][50][51][52][53][54], in 2 dimensions [55][56][57], and even in 3 dimensions [58]. Those models have provided new insights about the importance of cell interactions; however, they have not tested the importance of dormant cells (with their subthreshold signaling) [10][11][12], cells operating at low rates found in intact SAN [8], and autonomic modulation.…”
Section: A Broader Interpretation Of Our Results Toward Synchronization Mechanisms Of Cell Signaling In Intact San: Cell Specialization Amentioning
confidence: 99%
“…Multicellular numerical models of SAN function have been developed in 1 dimension (as a linear chain of consecutive SAN cells) [49][50][51][52][53][54], in 2 dimensions [55][56][57], and even in 3 dimensions [58]. Those models have provided new insights about the importance of cell interactions; however, they have not tested the importance of dormant cells (with their subthreshold signaling) [10][11][12], cells operating at low rates found in intact SAN [8], and autonomic modulation.…”
Section: A Broader Interpretation Of Our Results Toward Synchronization Mechanisms Of Cell Signaling In Intact San: Cell Specialization Amentioning
confidence: 99%
“…It should be emphasized that synchronization denotes that the system of cells becomes entrained to a stable periodicity, not necessarily that all cells match the rate of any individual cell’s activity. Multiple studies have indicated that the rate at which systems of pacemaker cells synchronize is a complex function of the independent activities of the coupled cells and not merely a convergence to the cycle length of the fastest cell in the system [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. For example, Mata et al showed that the more heterogeneous cardiac pacemaker cells (CPCs), the shorter the cycle length at which they synchronize [ 43 ].…”
Section: Electro-anatomical Features That Support Sinoatrial Node Functionmentioning
confidence: 99%
“…Furthermore, the influence of the coupled atrial tissue is not typically considered when examining the process of synchronization. As described below, computational treatments of sinoatrial node function are continually adding increased complexity to our view of heterogeneity, including variations in gap junctional conductivities, ion channel conductance [ 45 ], cellular make up [ 46 , 47 ] and cell-to-cell connectivity [ 43 ]. In particular, recent models introduced by Gratz et al, Ly and Weinberg, Mata et al, and Sehgal et al may be able to account for all these features in future analysis of synchronization [ 43 , 45 , 46 , 48 ].…”
Section: Electro-anatomical Features That Support Sinoatrial Node Functionmentioning
confidence: 99%
“…Testing new ideas and establishing exact mechanisms require new theoretical modeling. Multicellular numerical models of SAN function have been developed in 1 dimension (as a linear chain of consecutive SAN cells) [49][50][51][52][53][54], in 2 dimensions [55][56][57] and even in 3 dimensions [58]. Those models have provided new insights about the importance of cell interactions, but they have not tested importance of dormant cells (with their subthreshold signaling) [10][11][12], cells operating at low rates found in intact SAN [8], and autonomic modulation.…”
Section: A Broader Interpretation Of Our Results Towards Synchronization Mechanisms Of Cell Signaling In Intact San: Cell Specialization mentioning
confidence: 99%